2019
DOI: 10.1111/jgs.16092
|View full text |Cite
|
Sign up to set email alerts
|

High‐Sensitive Troponin T, Natriuretic Peptide, and Cognitive Change

Abstract: OBJECTIVES Cardiac troponin T, measured using a high‐sensitive assay (hs‐cTnT), and N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) are associated with increased stroke risk and perhaps with cognitive decline. However, few well‐designed prospective studies with extended follow‐up have been conducted. We aimed to estimate the association of hs‐cTnT and NT‐proBNP with 15‐year cognitive change in the Atherosclerosis Risk in Communities (ARIC) study. DESIGN Prospective cohort study. SETTING Four US communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
1
11
1
Order By: Relevance
“…70 The findings summarized above are somewhat contrasted by the results of the ARIC study, which revealed no independent association of NT-proBNP with 15-year change in three cognitive tests of executive function, verbal learning memory, and semantic fluency in a cohort of > 9000 participants. 71 In this study, only in a post hoc analysis the combination of NT-proBNP and hs-cTnT was associated with cognitive decline. Regarding MR-proANP, an association of elevated plasma concentrations of MR-proANP at baseline was associated with higher risk of incident all-cause dementia and VaD, but not AD in a population-based cohort of 5347 community-dwelling older adults.…”
Section: Natriuretic Peptides and Cognitive Impairmentmentioning
confidence: 59%
See 2 more Smart Citations
“…70 The findings summarized above are somewhat contrasted by the results of the ARIC study, which revealed no independent association of NT-proBNP with 15-year change in three cognitive tests of executive function, verbal learning memory, and semantic fluency in a cohort of > 9000 participants. 71 In this study, only in a post hoc analysis the combination of NT-proBNP and hs-cTnT was associated with cognitive decline. Regarding MR-proANP, an association of elevated plasma concentrations of MR-proANP at baseline was associated with higher risk of incident all-cause dementia and VaD, but not AD in a population-based cohort of 5347 community-dwelling older adults.…”
Section: Natriuretic Peptides and Cognitive Impairmentmentioning
confidence: 59%
“…There is also evidence suggesting that the link between high BNP and dementia may be age dependent, as it was only observed in people aged <79 years in one study 70 . The findings summarized above are somewhat contrasted by the results of the ARIC study, which revealed no independent association of NT‐proBNP with 15‐year change in three cognitive tests of executive function, verbal learning memory, and semantic fluency in a cohort of > 9000 participants 71 . In this study, only in a post hoc analysis the combination of NT‐proBNP and hs‐cTnT was associated with cognitive decline.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…cTnT is one of the cardiac calmodulin subunits and a specific marker of myocardial injury [ 25 , 26 ]. When myocardial cells damaged, with the rupture of cell membrane structure, cTnT quickly enters circulation [ 27 , 28 ]. The continuous progress of the production technology has continuously improved the detection level of cTnT [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of 2 well-established cardiac biomarkers, highsensitivity cardiac troponin (hs-TnT) and Nterminal pro-B-type natriuretic peptide (NT-proBNP), have classically been found to be elevated in patients with cardiomyocyte damage and stretch (heart failure), respectively. 2 They are also associated with an increased risk for heart failure and mortality in the general population as well as an increased risk for mortality and heart failure hospitalization in patients with heart failure. 3 Thus, cardiac biomarkers have potential to bring a greater level of precision to the cardiac care of patients with CKD.…”
mentioning
confidence: 99%